The Potency of Passion Fruit (Passiflora Edulis) Prevents Uv-Induced Skin Aging - Sherla Wijoyo; Ida Ayu Ika Wahyuniari (Postgraduate, University of Mataram, 2023)
The importance of skin health and appearance has led to increased awareness of the negative effects of skin aging induce by UV light. This research aims to examine the effect of passion fruit (Passiflora edulis) in preventing photoaging. Google Scholar, Research Gate, and Mendeley were used as the search engine. The keywords were passion fruit and photoaging. The effect of passion fruit to prevent photoaging were analyzed from 15 articles. The antioxidant contained in passion fruit has been reported and showed can suppress Reactive Oxygen SpeciesÂ Â (ROS), anti-inflammation activity, inhibit melanin synthesis and tyrosinase activity. This will contribute to prevention skin aging and skin damage by UV exposure